Low-expansion and high-stability porous silicon carbon negative electrode and preparation method and application thereof
By grinding into a nano-silicon alloy in a lithium-ion battery and performing multi-layer carbon structure treatment, the problem of low cycling stability of silicon carbon negative electrode is solved, and a low expansion and high stability porous silicon carbon negative electrode is achieved, which improves the circulation capacity of the battery and electrode stability.
Patent Information
- Application Number
- CN202411350578.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The cycling stability of silicon carbon anode in lithium-ion batteries is low, resulting in volume expansion and damage to the electrode structure, increasing the SEI layer, and reducing the embedding and deembedding efficiency of Li+.
The nano-silicon alloy was formed by grinding, and the nano-silicon alloy was coated with polydiallyl dimethyl ammonium chloride, and further coated by resin and vulcanization to form a porous structure, and mixed with carbon nanotubes and asphalt at high temperatures. A multi-layer carbon structure is formed to support the silicon, reducing expansion and side reactions.
A low expansion and high stability porous silicon carbon negative electrode is achieved, which improves the transmission efficiency of Li+ and the retention rate of the cycle capacity of the battery, and extends the service life of the electrode.
Smart Images

Figure CN119208566A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a low-expansion and highly stable porous silicon-carbon negative electrode and a preparation method and application thereof. Background Art
[0002] For lithium-ion battery negative electrode materials, silicon-based negative electrodes are considered to be potential and promising alternatives to graphite negative electrodes. However, volume expansion will inevitably occur during the charge and discharge process, which will destroy the physical structure of the battery material and affect its electrochemical performance. This problem has become a limiting factor in the practical application of silicon negative electrode materials. Excessive volume changes will lead to irreversible damage to the mechanical structure of the electrode. The electrolyte will enter the structure due to rupture. When the internal structure contacts the electrolyte, a new SEI layer is formed on the surface of the structure, which increases the electrolyte consumption. The loss of electrolyte and the increase of SEI layer hinder the Li + The embedding and de-embedding further reduce the Coulombic efficiency.
[0003] Therefore, the silicon-carbon negative electrode faces problems such as low conductivity and high expansion rate. The effective solution is pore creation and carbon coating. Since the expansion rates of carbon and silicon are inconsistent, the conventional carbon coating method is difficult to ensure the stability of the conductive network in long-term electrochemical cycles. Summary of the invention
[0004] The purpose of the present invention is to provide a low-expansion and high-stability porous silicon-carbon negative electrode and a preparation method and application thereof, so as to solve the technical problem of low cycle stability of silicon-carbon negative electrodes in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a porous silicon-carbon negative electrode with low expansion and high stability, comprising the following steps:
[0007] Step (1) mixing silicon powder, metal powder A, metal powder B, additives and grinding media to obtain a mixture, and ball milling the mixture to obtain a nano-silicon alloy;
[0008] Step (2) mixing the nano silicon alloy and the polydiallyldimethylammonium chloride solution, continuously stirring, filtering, washing, and drying to obtain a modified silicon alloy;
[0009] In the above process, polydiallyldimethylammonium chloride is coated on the surface of the nano-silicon alloy to obtain a positively charged nano-silicon alloy, thereby improving the dispersibility of the nano-silicon alloy and enhancing the compatibility and adhesion of the nano-silicon alloy with subsequent materials.
[0010] Step (3) mixing the modified silicon alloy prepared in step (2) with ammonia solution, resorcinol and water, ultrasonically treating the mixture, adding formaldehyde aqueous solution, stirring, standing, adding acetone, centrifuging, filtering, washing and drying to obtain a resin-coated silicon alloy;
[0011] In the above process, acetone is added to selectively dissolve the resin and control the thickness of the resin to prepare a resorcinol-formaldehyde resin-coated silicon alloy with an egg yolk shell structure.
[0012] Step (4) mixing the resin-coated silicon alloy, hexadecyltrimethylammonium bromide and anhydrous methanol, ultrasonically treating, adding 2-methylimidazole, and continuing the ultrasonic treatment to obtain solution A; adding Co(NO3)2·6H2O to anhydrous methanol, stirring to obtain solution B; adding solution B to solution A, stirring, and then slowly stirring to obtain a metal frame-coated silicon alloy;
[0013] In the above process, the resin-coated silicon alloy is wrapped in the zeolite imidazole framework.
[0014] Step (5) adding the metal frame coated silicon alloy and thioacetamide to ethanol, ultrasonically stirring, reacting, and drying to obtain a sulfide coated silicon alloy; adding the sulfide coated silicon alloy and Tris buffer to water, ultrasonically treating, and then adding dopamine hydrochloride and carbon nanotubes, stirring, filtering, and washing to obtain a dopamine coated silicon alloy;
[0015] In the above process, the resin-coated silicon alloy is encapsulated in Co9S8 through solvent thermal reaction vulcanization.
[0016] Step (6) The dopamine-coated silicon alloy is mixed with nanographite powder and asphalt, stirred, and then reacted in an argon atmosphere, etched with a saturated ethanol solution of ammonium chloride, washed, and dried to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0017] In the above process, after acid etching, the magnesium / zinc and magnesium oxide / zinc oxide are removed, leaving holes in the silicon alloy, leaving a porous silicon-tin / lead alloy, and after washing and drying, a low-expansion and highly stable porous silicon-carbon negative electrode is obtained.
[0018] Preferably, in step (1), the additive is 0.03-0.5wt% halogenated hydrocarbon, and the halogenated hydrocarbon is one of ethyl chloride, propyl chloride, ethyl bromide, and propyl bromide; the metal powder A includes at least one of Mg or Zn; the metal powder B includes at least one of Pb or Sn; the parameters of the ball milling treatment are: the ball milling speed is 100-450r / min, the ball-to-material ratio is 1:(6-10), and the ball milling time is 8-10h; the mass ratio of metal powder A to Si is Mg:Si=(12-48):28, Zn:Si=(6.5-21.5):28; the mass ratio of metal powder B to Si is Sn:Si=(1.2-5.9):28, Pb:Si=(2.1-10.4):28; the grinding medium is one of ethanol, isopropanol, n-butanol, and ethyl acetate; and the solid content of the mixture is 5-30wt%.
[0019] Preferably, in the step (2), the dosage ratio of the nano-silicon alloy and the polydiallyldimethylammonium chloride solution is (50-100) g: (2-4) L; the mass fraction of the polydiallyldimethylammonium chloride solution is 25 wt%; the continuous stirring time is 2-4 h; the washing method is washing with ethanol for 3-5 times; and the drying method is drying at 55-65° C. for 9-11 h.
[0020] Preferably, in the step (3), the dosage ratio of ammonia solution, resorcinol, water, formaldehyde aqueous solution and acetone is (25-50) mL: (40-80) g: (25-50) L: (40-80) mL: (20-40) mL; the mass fraction of ammonia solution is 25 wt%; the mass fraction of formaldehyde aqueous solution is 30 wt%; the ultrasonic treatment time is 25-35 min; the stirring time is 5-7 h; the standing time is 8-14 h; the centrifugal conditions are: the centrifugal speed is 2000-3000 r / min, the centrifugal temperature is 55-65° C., and the centrifugal time is 8-12 min; the washing method is: the filter residue is washed with water 3-5 times; the drying method is: dried at 75-85° C. for 9-11 h.
[0021] Preferably, in the step (4), the amount of resin-coated silicon alloy, hexadecyltrimethylammonium bromide, anhydrous methanol and 2-methylimidazole is (25-50) g: (15-30) g: (50-100) L: (1.6-3.2) kg; the ultrasonic treatment time is 25-35 min; the continued ultrasonic treatment time is 25-35 min; the amount ratio of Co(NO3)2·6H2O and anhydrous methanol is 1.4-2.8 kg: 50-100 L; the stirring time is 25-35 min; the stirring treatment time is 8-12 min; and the slow stirring time is 20-28 h.
[0022] Preferably, in the step (5), the amount ratio of the metal frame coated silicon alloy, thioacetamide, ethanol, sulfide coated silicon alloy, Tris buffer, water, dopamine hydrochloride, and carbon nanotubes is (10-20) g: (30-60) g: (5-10) L: (5-10) g: (5-10) g: (5-10) L: (10-20) g: (0.5-1) g; the ultrasonic stirring time is 25-35 min; the reaction conditions are: the reaction temperature is 115-125° C., and the reaction time is 5-7 h; the drying method is: drying at 75-85° C. for 9-11 h; the ultrasonic treatment time is 25-35 min; the stirring time is 20-28 h; and the washing method is: washing with ethanol 3-5 times.
[0023] Preferably, in step (6), the mass ratio of dopamine-coated silicon alloy, asphalt and nano-graphite powder is (850-1100):(40-50):(15-20); stirring conditions: stirring temperature is 100-120°C, stirring speed is 600-1200r / min, and stirring time is 10-30min; reaction conditions: reaction temperature is 700-900°C, and reaction time is 2-4h.
[0024] The low-expansion and high-stability porous silicon-carbon negative electrode is prepared by the method for preparing the low-expansion and high-stability porous silicon-carbon negative electrode.
[0025] Preferably, the present invention also provides application of the low-expansion and high-stability porous silicon-carbon negative electrode in lithium-ion batteries.
[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0027] 1. The present invention introduces metal magnesium / zinc and tin / lead during grinding to form an alloy with silicon; tin / lead is added to the silicon alloy to form an alloy with silicon, thereby reducing the crystallinity of silicon, which is beneficial to reducing the embedding barrier of lithium ions; after the metal magnesium and zinc are added to the silicon alloy, after acid etching, pores are left in the silicon, providing expansion space for silicon during the lithiation process, and the developed and uniform pore structure fully adapts to the volume change of silicon, shortens the diffusion path of ions, and is beneficial to ion transmission; the additive halogenated hydrocarbon can provide carbon cations during the mechanochemical grinding process, promote the surface alkylation of silicon, and prevent silicon from being oxidized; the addition of grinding media causes the surface dangling bonds of silicon to undergo electrophilic substitution reaction with alcohol during the silicon grinding process, which will destroy the Si-Si bond, increase the exposed surface of silicon, and cause silicon to be continuously oxidized, and the added magnesium / zinc can serve as a stronger electrophilic center to replace the direct reaction of silicon with alcohol, and passivate the silicon surface to prevent the bulk silicon from being further oxidized.
[0028] 2. In the present invention, a yolk-shell structured resin-coated silicon alloy is prepared by a room temperature solution, thereby avoiding the use of HF and its high pollution and toxicity; the resin-coated silicon alloy with a silicon-carbon shell-shell structure is wrapped in a zeolite imidazole skeleton, and then the resin-coated silicon alloy is wrapped in Co9S8 by vulcanization and carbon coating. The synergistic effect of the silicon alloy and the Co9S8 material alleviates the volume effect of silicon during the charging and discharging process; the dopamine-coated silicon alloy is mixed with nano-graphite powder and asphalt for coating and granulation and high-temperature carbonization, and dopamine is polymerized on the surface of the silicon alloy and converted into a carbon layer under high temperature conditions. The obtained multi-layer carbon layer serves as a supporting structure to prevent the internal silicon from expanding too much and causing structural fracture, while reducing the occurrence of side reactions and enhancing the structural stability of the composite material; at the same time, a large number of pore structures effectively increase the specific surface area, allowing the electrolyte to better penetrate into the electrode material, thereby improving Li + transmission efficiency in electrode materials and electrolytes; at the same time, due to the lack of active groups on the surface of carbon nanotubes (CNTs), the binding force between carbon nanotubes and silicon is weak when compounded with silicon. The expansion of silicon after lithium charging will destroy this bond. Polymerized dopamine acts as an adhesive to improve the binding force between silicon and carbon nanotubes, forming a cross-linked flexible conductive network structure, effectively alleviating the volume expansion of silicon and improving the rate performance of the material; mixed graphite and asphalt can reduce the specific surface area and reduce side reactions, thereby increasing the stacking density of electrode materials and the volume energy density of batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a schematic diagram of the structure of the low expansion and high stability porous silicon-carbon negative electrode of the present invention;
[0031] Figure 2 This is a process flow chart of the preparation of the low expansion and high stability porous silicon-carbon negative electrode of the present invention;
[0032] Figure 3 It is a bar graph of the first coulombic efficiency and 50 cycle capacity retention rate of the low expansion and high stability porous silicon-carbon negative electrode of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] See also Figure 1 , Figure 2 As shown, this embodiment discloses a method for preparing a low-expansion and highly stable porous silicon-carbon negative electrode, comprising the following steps:
[0036] Step (1) 84 g of silicon powder, 54 g of Mg, 19.2 g of Pb, 4.7 g of ethyl chloride and 1.9 L of ethanol were mixed to obtain a mixture, and the mixture was ball-milled at a rotation speed of 300 r / min and a ball-to-material ratio of 1:8 for 9 h to obtain a nano-silicon alloy;
[0037] Step (2) 75 g of nano-silicon alloy and 3 L of 25 wt% polydiallyldimethylammonium chloride solution were mixed, stirred continuously for 3 h, filtered, washed with ethanol 4 times, and dried at 60° C. for 10 h to obtain a modified silicon alloy;
[0038] Step (3) 38 mL of 25 wt% ammonia solution, 60 g of resorcinol, and 37 L of water were mixed with the modified silicon alloy, and ultrasonically treated for 30 min, and then 60 mL of 30 wt% formaldehyde aqueous solution was added, stirred for 6 h, and allowed to stand for 11 h, and then 30 mL of acetone was added, and the mixture was centrifuged at 2500 r / min at 60° C. for 10 min, filtered, and the filter residue was washed with water 4 times, and dried at 80° C. for 10 h to obtain a resin-coated silicon alloy;
[0039] Step (4) 38 g of resin-coated silicon alloy, 22 g of hexadecyltrimethylammonium bromide and 75 L of anhydrous methanol were mixed, ultrasonically treated for 30 min, and then 2.4 kg of 2-methylimidazole was added, and the ultrasonic treatment was continued for 30 min to obtain solution A; 2.1 kg of Co(NO3)2·6H2O was added to 75 L of anhydrous methanol, and stirred for 30 min to obtain solution B; solution B was added to solution A, stirred for 10 min, and then slowly stirred for 24 h to obtain a metal frame-coated silicon alloy;
[0040] Step (5) adding 15 g of the metal frame coated silicon alloy and 45 g of thioacetamide to 7.5 L of ethanol, ultrasonically stirring for 30 min, then reacting at 120° C. for 6 h, and drying at 80° C. for 10 h to obtain a sulfide coated silicon alloy; adding 7.5 g of the sulfide coated silicon alloy and 7.5 g of Tris buffer to 7.5 L of water, ultrasonically treating for 30 min, then adding 15 g of dopamine hydrochloride and 0.75 g of carbon nanotubes, stirring for 24 h, mixing, filtering, and washing with ethanol 4 times to obtain a dopamine coated silicon alloy;
[0041] Step (6) 9.8 g of dopamine-coated silicon alloy, 0.45 g of nano-graphite powder and 0.17 g of asphalt are stirred at 110°C at a speed of 800 r / min for 15 min, then reacted at 800°C in an argon atmosphere for 3 h, etched with a saturated ethanol solution of ammonium chloride for 3 h, washed with water 4 times, and dried at 80°C to constant weight to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0042] Example 2
[0043] See also Figure 1 , Figure 2 As shown, this embodiment discloses a method for preparing a low-expansion and highly stable porous silicon-carbon negative electrode, comprising the following steps:
[0044] Step (1) 84 g of silicon powder, 22.5 g of Zn, 10.7 g of Sn, 1.2 g of ethyl chloride and 1.3 L of isopropanol were mixed to obtain a mixture, and the mixture was ball-milled at a rotation speed of 450 r / min and a ball-to-material ratio of 1:6 for 10 h to obtain a nano-silicon alloy;
[0045] Step (2) 50 g of nano-silicon alloy and 4 L of 25 wt% polydiallyldimethylammonium chloride solution were mixed, stirred continuously for 4 h, filtered, washed with ethanol 3 times, and dried at 65° C. for 9 h to obtain a modified silicon alloy;
[0046] Step (3) 50 mL of 25 wt% ammonia solution, 40 g of resorcinol, and 50 L of water were mixed with the modified silicon alloy, and ultrasonic treatment was performed for 25 min, and then 80 mL of 30 wt% formaldehyde aqueous solution was added, stirred for 5 h, and allowed to stand for 14 h, and then 20 mL of acetone was added, and the mixture was centrifuged at 2000 r / min at 65 ° C for 12 min, filtered, and the filter residue was washed with water for 3 times, and dried at 85 ° C for 9 h to obtain a resin-coated silicon alloy;
[0047] Step (4) 50 g of resin-coated silicon alloy, 15 g of hexadecyltrimethylammonium bromide and 100 L of anhydrous methanol were mixed, ultrasonically treated for 25 min, and then 3.2 kg of 2-methylimidazole was added, and the ultrasonic treatment was continued for 25 min to obtain solution A; 2.8 kg of Co(NO3)2·6H2O was added to 50 L of anhydrous methanol, and stirred for 35 min to obtain solution B; solution B was added to solution A, stirred for 8 min, and then slowly stirred for 28 h to obtain a metal frame-coated silicon alloy;
[0048] Step (5) adding 10 g of the metal frame coated silicon alloy and 60 g of thioacetamide to 5 L of ethanol, ultrasonically stirring for 35 min, then reacting at 115° C. for 5 h, and drying at 85° C. for 9 h to obtain a sulfide coated silicon alloy; adding 10 g of the sulfide coated silicon alloy and 5 g of Tris buffer to 10 L of water, ultrasonically treating for 25 min, then adding 20 g of dopamine hydrochloride and 0.5 g of carbon nanotubes and stirring for 20 h, mixing, filtering, and washing with ethanol 5 times to obtain a dopamine coated silicon alloy;
[0049] Step (6) 8.5 g of dopamine-coated silicon alloy, 0.5 g of nano-graphite powder and 0.15 g of asphalt are stirred at 120°C at a speed of 600 r / min for 30 min, then reacted at 700°C in an argon atmosphere for 4 h, etched with a saturated ethanol solution of ammonium chloride for 2 h, washed with water 5 times, and dried at 75°C to constant weight to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0050] Example 3
[0051] See also Figure 1 , Figure 2 As shown, this embodiment discloses a method for preparing a low-expansion and highly stable porous silicon-carbon negative electrode, comprising the following steps:
[0052] Step (1) 84 g of silicon powder, 36 g of Mg, 17 g of Sn, 2.7 g of propylene glycol and 1.6 L of n-butanol were mixed to obtain a mixture, and the mixture was ball-milled at a rotation speed of 100 r / min and a ball-to-material ratio of 1:10 for 8 h to obtain a nano-silicon alloy;
[0053] Step (2) 100 g of nano-silicon alloy and 2 L of 25 wt% polydiallyldimethylammonium chloride solution were mixed, stirred continuously for 2 h, filtered, washed with ethanol 5 times, and dried at 55° C. for 11 h to obtain a modified silicon alloy;
[0054] Step (3) 25 mL of 25 wt% ammonia solution, 80 g of resorcinol, and 25 L of water were mixed with the modified silicon alloy, and ultrasonic treatment was performed for 35 min, and then 40 mL of 30 wt% formaldehyde aqueous solution was added, stirred for 7 h, and allowed to stand for 8 h, and then 40 mL of acetone was added, and the mixture was centrifuged at 3000 r / min at 55 ° C for 8 min, filtered, and the filter residue was washed with water for 5 times, and dried at 75 ° C for 11 h to obtain a resin-coated silicon alloy;
[0055] Step (4) 25 g of resin-coated silicon alloy, 30 g of hexadecyltrimethylammonium bromide and 50 L of anhydrous methanol were mixed, ultrasonically treated for 35 min, and then 1.6 kg of 2-methylimidazole was added, and the ultrasonic treatment was continued for 35 min to obtain solution A; 1.4 kg of Co(NO3)2·6H2O was added to 100 L of anhydrous methanol, and stirred for 25 min to obtain solution B; solution B was added to solution A, stirred for 12 min, and then slowly stirred for 20 h to obtain a metal frame-coated silicon alloy;
[0056] Step (5) adding 20 g of the metal frame coated silicon alloy and 30 g of thioacetamide to 10 L of ethanol, ultrasonically stirring for 25 min, then reacting at 125° C. for 5 h, and drying at 85° C. for 9 h to obtain a sulfide coated silicon alloy; adding 10 g of the sulfide coated silicon alloy and 5 g of Tris buffer to 10 L of water, ultrasonically treating for 25 min, then adding 20 g of dopamine hydrochloride and 1 g of carbon nanotubes, stirring for 20 h, mixing, filtering, and washing with ethanol 5 times to obtain a dopamine coated silicon alloy;
[0057] Step (6) 8.5 g of dopamine-coated silicon alloy, 0.5 g of nano-graphite powder and 0.15 g of asphalt are stirred at 120°C at a speed of 600 r / min for 30 min, then reacted at 700°C in an argon atmosphere for 4 h, etched with a saturated ethanol solution of ammonium chloride for 2 h, washed with water 5 times, and dried at 75°C to constant weight to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0058] Example 4
[0059] See also Figure 1 , Figure 2 As shown, this embodiment discloses a method for preparing a low-expansion and highly stable porous silicon-carbon negative electrode, comprising the following steps:
[0060] Step (1) 84 g of silicon powder, 64 g of Zn, 7 g of Pb, 6 g of ethyl bromide and 1.8 L of ethyl acetate are mixed to obtain a mixture, and the mixture is ball-milled at a rotation speed of 400 r / min and a ball-to-material ratio of 1:7 for 9 h to obtain a nano-silicon alloy;
[0061] Step (2) 60 g of nano-silicon alloy and 3.2 L of 25 wt% polydiallyldimethylammonium chloride solution were mixed, stirred continuously for 3 h, filtered, washed with ethanol 4 times, and dried at 60° C. for 10 h to obtain a modified silicon alloy;
[0062] Step (3) 40 mL of 25 wt% ammonia solution, 50 g of resorcinol and 30 L of water were mixed with the modified silicon alloy, and ultrasonic treatment was performed for 28 min, and then 70 mL of 30 wt% formaldehyde aqueous solution was added, stirred for 6 h, and allowed to stand for 12 h, and then 25 mL of acetone was added, and the mixture was centrifuged at 2200 r / min at 60° C. for 11 min, filtered, and the filter residue was washed with water 4 times, and dried at 80° C. for 10 h to obtain a resin-coated silicon alloy;
[0063] Step (4) 45 g of resin-coated silicon alloy, 20 g of hexadecyltrimethylammonium bromide and 85 L of anhydrous methanol were mixed, ultrasonically treated for 30 min, and then 3 kg of 2-methylimidazole was added, and the ultrasonic treatment was continued for 28 min to obtain solution A; 2.6 kg of Co(NO3)2·6H2O was added to 60 L of anhydrous methanol and stirred for 30 min to obtain solution B; solution B was added to solution A, stirred for 9 min, and then slowly stirred for 26 h to obtain a metal frame-coated silicon alloy;
[0064] Step (5) adding 13 g of the metal frame coated silicon alloy and 50 g of thioacetamide to 6 L of ethanol, ultrasonically stirring for 33 min, then reacting at 118 ° C. for 6 h, and drying at 78 ° C. for 10 h to obtain a sulfide coated silicon alloy; adding 6 g of the sulfide coated silicon alloy and 9 g of Tris buffer to 6 L of water, ultrasonically treating for 32 min, then adding 12 g of dopamine hydrochloride and 0.6 g of carbon nanotubes, stirring for 26 h, mixing, filtering, and washing with ethanol 4 times to obtain a dopamine coated silicon alloy;
[0065] Step (6) 1 g of dopamine-coated silicon alloy is stirred with 0.4 g of nano-graphite powder and 0.2 g of asphalt at 105°C and a speed of 1100 r / min for 15 min, and then reacted at 850°C in an argon atmosphere for 3 h. After etching with a saturated ethanol solution of ammonium chloride for 3 h, it is washed with water 4 times and dried at 80°C to constant weight to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0066] Example 5
[0067] See also Figure 1 , Figure 2 As shown, this embodiment discloses a method for preparing a low-expansion and highly stable porous silicon-carbon negative electrode, comprising the following steps:
[0068] Step (1) 84 g silicon powder, 144 g Mg, 3.6 g Sn, 3.5 g bromopropane and 1.2 L ethanol were ball milled at a speed of 200 r / min and a ball-to-material ratio of 1:9 for 9 h to obtain a nano-silicon alloy;
[0069] Step (2) 90 g of nano-silicon alloy and 2.2 L of 25 wt% polydiallyldimethylammonium chloride solution were mixed, stirred continuously for 3 h, filtered, washed with ethanol 4 times, and dried at 60° C. for 10 h to obtain a modified silicon alloy;
[0070] Step (3) 38 mL of 25 wt% ammonia solution, 70 g of resorcinol, and 30 L of water were mixed with the modified silicon alloy, and ultrasonically treated for 30 min, and then 50 mL of 30 wt% formaldehyde aqueous solution was added, stirred for 6 h, and allowed to stand for 9 h, and then 35 mL of acetone was added, and the mixture was centrifuged at 2800 r / min at 60° C. for 9 min, filtered, and the filter residue was washed with water 4 times, and dried at 80° C. for 10 h to obtain a resin-coated silicon alloy;
[0071] Step (4) 26 g of resin-coated silicon alloy, 28 g of hexadecyltrimethylammonium bromide and 60 L of anhydrous methanol were mixed, ultrasonically treated for 30 min, and then 1.8 kg of 2-methylimidazole was added, and the ultrasonic treatment was continued for 30 min to obtain solution A; 1.6 kg of Co(NO3)2·6H2O was added to 90 L of anhydrous methanol, and stirred for 30 min to obtain solution B; solution B was added to solution A, stirred for 11 min, and then slowly stirred for 22 h to obtain a metal frame-coated silicon alloy;
[0072] Step (5) adding 18 g of the metal frame coated silicon alloy and 40 g of thioacetamide to 7.5 L of isopropanol, ultrasonically stirring for 30 min, then reacting at 120 ° C for 6 h, and drying at 80 ° C for 10 h to obtain a sulfide coated silicon alloy; adding 7 g of the sulfide coated silicon alloy and 6 g of Tris buffer to 9 L of water, ultrasonically treating for 28 min, then adding 12 g of dopamine hydrochloride and 0.9 g of carbon nanotubes, stirring for 22 h, mixing, filtering, and washing with ethanol 4 times to obtain a dopamine coated silicon alloy;
[0073] Step (6) 9 g dopamine-coated silicon alloy, 0.5 g nano-graphite powder and 0.2 g asphalt are stirred at 115 ° C and 700 r / min for 25 min, then reacted at 750 ° C in an argon atmosphere for 3 h, etched with a saturated ethanol solution of ammonium chloride for 3 h, washed with water 4 times, and dried at 80 ° C to constant weight to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0074] Example 6
[0075] See also Figure 1 , Figure 2As shown, this embodiment discloses a method for preparing a low-expansion and highly stable porous silicon-carbon negative electrode, comprising the following steps:
[0076] Step (1) 84 g of silicon powder, 19.5 g of Zn, 31.2 g of Pb, 1.6 g of ethyl chloride and 0.8 L of ethanol were mixed to obtain a mixture, and the mixture was ball-milled at a rotation speed of 300 r / min and a ball-to-material ratio of 1:7 for 9 h to obtain a nano-silicon alloy;
[0077] Step (2) 90 g of nano-silicon alloy and 2.5 L of 25 wt% polydiallyldimethylammonium chloride solution were mixed, stirred continuously for 3 h, filtered, washed with ethanol 4 times, and dried at 60° C. for 10 h to obtain a modified silicon alloy;
[0078] Step (3) 30 mL of 25 wt% ammonia solution, 70 g of resorcinol, and 40 L of water were mixed with the modified silicon alloy, and ultrasonic treatment was performed for 30 min, and then 50 mL of 30 wt% formaldehyde aqueous solution was added, stirred for 6 h, and allowed to stand for 12 h, and then 25 mL of acetone was added, and the mixture was centrifuged at 2800 r / min at 60° C. for 11 min, filtered, and the filter residue was washed with water 4 times, and dried at 80° C. for 10 h to obtain a resin-coated silicon alloy;
[0079] Step (4) 45 g of resin-coated silicon alloy, 20 g of hexadecyltrimethylammonium bromide and 60 L of anhydrous methanol were mixed, ultrasonically treated for 30 min, and then 3 kg of 2-methylimidazole was added, and the ultrasonic treatment was continued for 30 min to obtain solution A; 1.8 kg of Co(NO3)2·6H2O was added to 90 L of anhydrous methanol, and stirred for 30 min to obtain solution B; solution B was added to solution A, stirred for 9 min, and then slowly stirred for 21 h to obtain a metal frame-coated silicon alloy;
[0080] Step (5) adding 18 g of the metal frame coated silicon alloy and 50 g of thioacetamide to 6 L of ethanol, ultrasonically stirring for 30 min, then reacting at 120 ° C for 6 h, and drying at 80 ° C for 10 h to obtain a sulfide coated silicon alloy; adding 8 g of the sulfide coated silicon alloy and 9 g of Tris buffer to 6 L of water, ultrasonically treating for 30 min, then adding 18 g of dopamine hydrochloride and 0.8 g of carbon nanotubes, stirring for 24 h, mixing, filtering, and washing with ethanol 4 times to obtain a dopamine coated silicon alloy;
[0081] Step (6) 9 g of dopamine-coated silicon alloy, 0.4 g of nano-graphite powder and 0.2 g of asphalt are stirred at 105°C at a speed of 700 r / min for 25 min, then reacted at 800°C for 3 h in an argon atmosphere, etched with a saturated ethanol solution of ammonium chloride for 3 h, washed with water 4 times, and dried at 80°C to constant weight to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0082] Comparative Example 1
[0083] Comparative Example 1 Compared with Example 1, in the process of preparing the low-expansion and high-stability porous silicon-carbon negative electrode in Comparative Example 1, no metal powder A was added, and other conditions remained unchanged.
[0084] Comparative Example 2
[0085] Comparative Example 2 Compared with Example 1, in the process of preparing the low-expansion and high-stability porous silicon-carbon negative electrode in Comparative Example 2, no metal powder B was added, and other conditions remained unchanged.
[0086] Comparative Example 3
[0087] Comparative Example 3 Compared with Example 1, in the process of preparing the low expansion and high stability porous silicon-carbon negative electrode in Example 3, no sulfide coated silicon alloy was obtained, that is, the dopamine coated silicon alloy was directly obtained from the nano silicon alloy obtained in step (1), and other conditions remained unchanged, as follows:
[0088] 84g silicon powder, 54g Mg, 19.2g Pb, 4.7g ethyl chloride and 1.9L ethanol were mixed to obtain a mixture, and the mixture was ball-milled at a speed of 300r / min and a ball-to-material ratio of 1:8 for 9h to obtain a nano-silicon alloy; 7.5g nano-silicon alloy and 7.5g Tris buffer were added to 7.5L water, ultrasonically treated for 30min, and then 15g dopamine hydrochloride was added and stirred for 24h. After mixing, it was filtered and washed with ethanol for 4 times to obtain a dopamine-coated silicon alloy; 9.8g dopamine-coated silicon alloy was stirred with 0.45g nano-graphite powder and 0.17g asphalt at 110°C and a speed of 800r / min for 15min, and then reacted at 800°C in an argon atmosphere for 3h, etched with a saturated ethanol solution of ammonium chloride for 3h, washed with water 4 times, and dried at 80°C to constant weight to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0089] Comparative Example 4
[0090] Comparative Example 4 Compared with Example 1, in the process of preparing the low expansion and high stability porous silicon-carbon negative electrode in Comparative Example 4, dopamine hydrochloride was not added, and other conditions remained unchanged, as follows:
[0091] Steps (1) to (4) remain unchanged, and then 15 g of the metal frame-coated silicon alloy and 45 g of thioacetamide are added to 7.5 L of ethanol, ultrasonically stirred for 30 min, and then reacted at 120 ° C for 6 h, and dried at 80 ° C for 10 h to obtain a sulfide-coated silicon alloy; 9.8 g of the sulfide-coated silicon alloy, 0.45 g of nano-graphite powder, and 0.17 g of asphalt are stirred at 110 ° C at a speed of 800 r / min for 15 min, and then reacted at 800 ° C in an argon atmosphere for 3 h. After etching with a saturated ethanol solution of ammonium chloride for 3 h, the mixture is washed with water 4 times and dried at 80 ° C to constant weight to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
[0092] Experimental example
[0093] The performance of the low expansion and high stability porous silicon-carbon negative electrodes prepared in Examples 1-6 and Comparative Examples 1-4 were tested.
[0094] Electrochemical performance test
[0095] The porous silicon-carbon negative electrode prepared in Examples 1-6 and Comparative Examples 1-4 and the counter electrode lithium sheet were used to make half-cells, and their related electrochemical properties were tested. The test results are shown in Table 1. Among them, the conductive agent is conductive carbon SuperP, the separator is celgard2400, and the electrolyte is DMC:DEC:EC (vol%)=1:1:1 solution containing 1mol / LLiPF6 conductive salt. The test conditions are: the charge and discharge cut-off voltage is 0.005-2V, the first reversible specific capacity is tested at 0.1C, and the charge and discharge cycle is 20 times at 0.2C. The test results are shown in Table 1.
[0096] Table 1
[0097]
[0098] It can be seen from Table 1 that the electrochemical performance of the low-expansion and high-stability porous silicon-carbon negative electrodes prepared in Examples 1-6 are much better than the electrochemical performance of the low-expansion and high-stability porous silicon-carbon negative electrodes prepared in Comparative Examples 1-4. By adopting the preparation method of the present invention, a porous silicon-carbon negative electrode with good cycle stability, good conductivity and high specific capacity can be obtained. From the comparison between comparative example 1 and example 1, it can be seen that in the process of preparing a porous silicon-carbon negative electrode with low expansion and high stability, the present invention adds metal powder A to improve the electrochemical performance of the porous silicon-carbon negative electrode with low expansion and high stability; from the comparison between comparative example 2 and example 1, it can be seen that in the process of preparing a porous silicon-carbon negative electrode with low expansion and high stability, the present invention adds metal powder B to improve the electrochemical performance of the porous silicon-carbon negative electrode with low expansion and high stability; from the comparison between comparative example 3 and example 1, it can be seen that in the process of preparing a porous silicon-carbon negative electrode with low expansion and high stability, the present invention forms a sulfide-coated silicon alloy to improve the electrochemical performance of the porous silicon-carbon negative electrode with low expansion and high stability; from the comparison between comparative example 4 and example 1, it can be seen that in the process of preparing a porous silicon-carbon negative electrode with low expansion and high stability, the present invention adds dopamine hydrochloride to improve the electrochemical performance of the porous silicon-carbon negative electrode with low expansion and high stability.
[0099] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0100] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a porous silicon-carbon negative electrode with low expansion and high stability, characterized in that: The following steps are involved: Step (1) mixing silicon powder, metal powder A, metal powder B, additives and grinding media to obtain a mixture, and ball milling the mixture to obtain a nano-silicon alloy; Step (2) mixing the nano silicon alloy and the polydiallyldimethylammonium chloride solution, continuously stirring, filtering, washing, and drying to obtain a modified silicon alloy; Step (3) mixing the modified silicon alloy prepared in step (2) with ammonia solution, resorcinol, water, and ultrasonic treatment, adding formaldehyde aqueous solution, stirring, standing, then adding acetone, centrifuging, filtering, washing, and drying to obtain a resin-coated silicon alloy; Step (4) mixing the resin-coated silicon alloy, hexadecyltrimethylammonium bromide and anhydrous methanol, ultrasonically treating the mixture, adding 2-methylimidazole, and continuing the ultrasonic treatment to obtain solution A; adding Co(NO3)2·6H2O to anhydrous methanol, stirring the mixture, and obtaining solution B; adding solution B to solution A, stirring the mixture, and then slowly stirring the mixture to obtain a metal frame-coated silicon alloy; Step (5) adding the metal frame coated silicon alloy and thioacetamide to ethanol, ultrasonically stirring, reacting, and drying to obtain a sulfide coated silicon alloy; adding the sulfide coated silicon alloy and Tris buffer to water, ultrasonically treating, and then adding dopamine hydrochloride and carbon nanotubes, stirring, filtering, and washing to obtain a dopamine coated silicon alloy; Step (6) The dopamine-coated silicon alloy is mixed with nanographite powder and asphalt, stirred, and then reacted in an argon atmosphere, etched with a saturated ethanol solution of ammonium chloride, washed, and dried to obtain a low-expansion and highly stable porous silicon-carbon negative electrode.
2. The method for preparing a low expansion and high stability porous silicon-carbon negative electrode according to claim 1, characterized in that: In the step (1), the additive is 0.03-0.5wt% of a halogenated hydrocarbon, and the halogenated hydrocarbon is one of ethyl chloride, propyl chloride, ethyl bromide, and propyl bromide; the metal powder A includes at least one of Mg or Zn; the metal powder B includes at least one of Pb or Sn; the parameters of the ball milling treatment are: the ball milling speed is 100-450r / min, the ball-to-material ratio is 1:(6-10), and the ball milling time is 8-10h; the mass ratio of the metal powder A to Si is Mg:Si=(12-48):28, Zn:Si=(6.5-21.5):28; the mass ratio of the metal powder B to Si is Sn:Si=(1.2-5.9):28, Pb:Si=(2.1-10.4):48; the grinding medium is one of ethanol, isopropanol, n-butanol, and ethyl acetate; and the solid content of the mixture is 5-30wt%.
3. The method for preparing a low expansion and high stability porous silicon-carbon negative electrode according to claim 1, characterized in that: In the step (2), the dosage ratio of the nano-silicon alloy and the polydiallyldimethylammonium chloride solution is (50-100) g: (2-4) L; the mass fraction of the polydiallyldimethylammonium chloride solution is 25 wt %; the continuous stirring time is 2-4 h; the washing method is to wash with ethanol for 3-5 times; and the drying method is to dry at 55-65° C. for 9-11 h.
4. The method for preparing a low expansion and high stability porous silicon-carbon negative electrode according to claim 1, characterized in that: In the step (3), the dosage ratio of ammonia solution, resorcinol, water, formaldehyde aqueous solution and acetone is (25-50) mL: (40-80) g: (25-50) L: (40-80) mL: (20-40) mL; the mass fraction of ammonia solution is 25 wt %; the mass fraction of formaldehyde aqueous solution is 30 wt %; the ultrasonic treatment time is 25-35 min; the stirring time is 5-7 h; the standing time is 8-14 h; the centrifugal conditions are: the centrifugal speed is 2000-3000 r / min, the centrifugal temperature is 55-65° C., and the centrifugal time is 8-12 min; the washing method is: the filter residue is washed with water for 3-5 times; the drying method is: dried at 75-85° C. for 9-11 h.
5. The method for preparing a low expansion and high stability porous silicon-carbon negative electrode according to claim 1, characterized in that: In the step (4), the amount of the resin-coated silicon alloy, hexadecyltrimethylammonium bromide, anhydrous methanol, and 2-methylimidazole is (25-50) g: (15-30) g: (50-100) L: (1.6-3.2) kg; the ultrasonic treatment time is 25-35 min; the continued ultrasonic treatment time is 25-35 min; the amount ratio of Co(NO3)2·6H2O and anhydrous methanol is 1.4-2.8 kg: 50-100 L; the stirring time is 25-35 min; the stirring treatment time is 8-12 min; and the slow stirring time is 20-28 h.
6. The method for preparing a low expansion and high stability porous silicon-carbon negative electrode according to claim 1, characterized in that: In the step (5), the amount ratio of the metal frame coated silicon alloy, thioacetamide, ethanol, sulfide coated silicon alloy, Tris buffer, water, dopamine hydrochloride, and carbon nanotubes is (10-20) g: (30-60) g: (5-10) L: (5-10) g: (5-10) g: (5-10) L: (10-20): (0.5-1) g; the ultrasonic stirring time is 25-35 min; the reaction conditions are: the reaction temperature is 115-125° C., and the reaction time is 5-7 h; the drying method is: drying at 75-85° C. for 9-11 h; the ultrasonic treatment time is 25-35 min; the stirring time is 20-28 h; and the washing method is: washing with ethanol 3-5 times.
7. The method for preparing a low expansion and high stability porous silicon-carbon negative electrode according to claim 1, characterized in that: In the step (6), the mass ratio of dopamine-coated silicon alloy, asphalt and nano-graphite powder is (850-1100):(40-50):(15-20); stirring conditions: stirring temperature is 100-120°C, stirring speed is 600-1200r / min, and stirring time is 10-30min; reaction conditions: reaction temperature is 700-900°C, and reaction time is 2-4h.
8. A low expansion and high stability porous silicon-carbon negative electrode prepared by the method according to any one of claims 1 to 7.
9. Application of the low expansion and high stability porous silicon-carbon negative electrode as claimed in claim 8 in lithium-ion batteries.
